Similar rates of relapse and time to return to normal activity with 2 or 5 days of systemic corticosteroids after asthma exacerbation but study confirmation of equivalence would require further study. Issue 1 (28th November 2011) - Rowe, Brian H
Abstract : Commentary on: Kravitz J Dominici P Ufberg J . Two days of dexamethasone versus 5 days of prednisone in the treatment of acute asthma: a randomized controlled trial. Ann Emerg Med 2011 ;58 :200 –4 .